Post-Covid Adaptation: Students' Mental Health and Higher Education System in Indonesia - Pandia, Weny Savitry S.; Suryani, Angela Oktavia; Irwanto, Irwanto (Rescollacom (Research Collaborations Community), 2023)
The pandemic brought many changes, including for students. Various negative things experienced by students have an impact on their mental health. However, there are coping mechanisms that can bring positive changes to students' lives and help them survive the post-pandemic period. This research aimed to explore: the problems, level of stress, coping mechanisms carried out by students, and resilience level during the pandemic; the student's mental health situation during post-pandemic; and the recommendation for higher education (HE) institutions to support students' mental health. The research included 5018 students in bachelor's programs from 20 universities of APTIK members via quota sampling method on gender and class year (stage 1); and reports from students about their psychological symptoms during classes (n = 5 classes) and counseling (n = 10 cases) and literature review from explore 13 articles via Google scholar and Google search engine (stage 2). The study results show that students had many learning and social life challenges. Students who can develop positive coping with stress will be resilient and benefit from the experience during the pandemic, such as increased online learning skills, health awareness, and good time management. A positive coping strategy empowers the students to develop good mental health and survive during the pandemic, together with the support of the education system in higher education institutions. The institution should provide leadership, a good governance system, conducive teaching and learning system, and an appreciation for diversity and inclusivity to support students' mental health. The system should support the various changes experienced by students. With a good strategy and governance, there will be clarity and comfort so that it does not exacerbate the mental health problems encountered by many students. The impact is that students are more prepared and confident to connect with the industry world.